2017
DOI: 10.1016/j.micres.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

An LRR receptor kinase regulates growth, development and pathogenesis in Phytophthora capsici

Abstract: Leucine-rich repeats (LRRs) domain containing kinase proteins (LRR-RK) perform various functions in eukaryotic organisms. However, their functions in Oomycetes are still largely unknown. Here, we identified an LRR-RK (PcLRR-RK1) gene and characterized its functions in Phytophthora capsici, a model oomycete specie and a major plant destroyer of solanaceous and cucurbitaceous vegetable crops. We showed that PcLRR-RK1-silenced P. capsici transformants exhibited reduced growth and produced highly branched fluffy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Expressed sequence tag analysis reveals that oomycete LRR-RLK-encoding genes are expressed during vegetative growth and host infection [14]. We recently reported that PcLRR-RK1 functions in Phytophthora capsici virulence and development of mycelium, sporangia, and zoospores ( Safdar et al., 2017 ). Only one to two RLKs can be found in species such as Hyaloperonospora parasitica and Pythium ultimum .…”
Section: Introductionmentioning
confidence: 99%
“…Expressed sequence tag analysis reveals that oomycete LRR-RLK-encoding genes are expressed during vegetative growth and host infection [14]. We recently reported that PcLRR-RK1 functions in Phytophthora capsici virulence and development of mycelium, sporangia, and zoospores ( Safdar et al., 2017 ). Only one to two RLKs can be found in species such as Hyaloperonospora parasitica and Pythium ultimum .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the silencing of a gene encoding a dynamin-related protein (PsVPS1) was reported to result in abnormal cyst germination and inhibited infections of soybean by Phytophthora sojae 25 . In Phytophthora capsici, leucine-rich repeat (LRR) domain-containing kinases contribute to sporangium formation, zoospore release, cyst germination, and infection of Nicotiana benthamiana 26 . Our preliminary analysis of transcription in the presence of Ī²-rubromycin during cyst germination indicated that the expression levels of genes encoding dynamin-like proteins (PITG_08836, 08837, and 08838) and an LRR receptor kinase gene (PITG_17495) were unaffected by Ī²-rubromycin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For silencing of RXLR25 in P. capsici , a specific sequence (545ā€“1278 bp) from RXLR25 was amplified and cloned into the pTOR vector and introduced into P. capsici LT263 by polyethylene glycol (PEG)ā€mediated protoplast transformation (Safdar et al ., 2017). Putative transformants were selected on V8 agar plates containing 30 Ī¼g ml āˆ’1 G418.…”
Section: Methodsmentioning
confidence: 99%